Efficacy of Bedside Index for Severity In Acute Pancreatitis (Bisap) Score As Predictor of In-Hospital Outcome in Acute Pancreatitis - Islam, Mohammad Sirajul; Hossain, Ahmed; Islam, Daharul; Abira, Mahmuda (Bangladesh Journal of Medicine, 2024)
Background: Acute pancreatitis is a potentially life-threatening condition characterized by inflammation of the pancreas. Early identification of patients at risk of severe disease is crucial for devising appropriate management strategies and improving outcomes. The aim of the study was to investigate the efficacy of BISAP score as predictor of in-hospital outcome in patients with acute pancreatitis. Methods: This was a longitudinal study conducted in Department of Medicine, Sir Salimullah Medical College Mitford Hospital, Dhaka from January 2023 to December 2023. After ethical approval, a total 107 subjects were included in this study based on inclusion and exclusion criteria. Severity of the disease was assessed by BISAP score. Theoutcome determinants were length of hospital stay, complete recovery, partial recovery with complication, transfer to ICU and mortality. Chi Square test, Binominal Regression analysis and Receiver operator characteristic (ROC) curve analysis were performed as applicable. p value <0.05 was considered as the level of significance. Results: The mean BISAP score among 107 study participants was 2.00 ± 0.76. Patients with BISAP score ³3 had significantly increased odds of prolonged hospital stay (OR: 11.226; 95% CI: 2.985- 42.222; p<0.001), higher rate of partial recovery with complications (OR: 7.302; 95.325% CI: -20.997; p<0.001). <0.001), and greater likelihood of intensive care unit (ICU) transfer (OR: 1.136; 95% CI: 0.968-1.333; p=0.004). A BISAP score cutoff value of ³3 was associated with increased length of hospital stay (sensitivity 91.3%, specificity 97.6%, AUC=0.945), partial recovery with complications (sensitivity 83.3%, specificity 96.4%, AUC=0.899), and ICU transfer (sensitivity 75%, specificity 80.6%, AUC=0.778).Conclusion: It can be concluded that increased BISAP score can be served as an independent predictor of in-hospital in patients with acute pancreatitis (AP). Bangladesh J Medicine 2024; 35: 88-92